Chronic alcohol consumption and COVID-19 infection risk: a narrative review - Friske, Marion; Spanagel, Rainer (Alcohol, 2023)
During the COVID-19 pandemic, many potential risk groups have been identified, such as those with obesity, diabetes, preexisting organ injuries, and several other conditions. Smoking is the most reported substance use disorder linked to increased COVID-19 hospitalization rate and disease severity. In relation to smoking, we discuss the impairment of the innate and the adaptive immune systems as being among the main potential reasons for increased COVID-19 infection risk and severity. Chronic alcohol consumption and alcohol use disorder (AUD) also have a negative impact on the immune system, but when it comes to COVID-19 risk, they produce diverse outcomes. Some studies provide evidence that chronic alcohol consumption and AUD increase the risk of COVID-19 infection and severe disease progression, while others report reduced hospitalization and death rates. In this review, we summarize the current state of epidemiological and molecular data concerning alcohol consumption and AUD as risk factors for COVID-19 infection, hospitalization, and mortality.
Online veröffentlicht: 27. Februar 2023
Gesehen am 15.02.2024